Treatment of Migraine With Phytocannabinoids, the Involvement of Endocannabinoids in Migraine, and Potential Mechanisms of Action - Roger Gregory Biringer (Pain Research and Management, 2025)
The American Migraine Foundation estimates that over 39 million Americans and over 1 billion people worldwide suffer from some form of migraine. Treatment of migraine generally falls into two categories: treatment of attacks once they have begun, and prophylactic prevention, including lifestyle changes. The use of phytocannabinoids to reduce both the frequency and severity of migraine is widely documented in scientific, grey, and popular literature. This review provides descriptions of both preclinical and clinical studies involving the treatment of migraines with phytocannabinoids as well as the involvement of endocannabinoids and endocannabinoid-like compounds in migraine pathology, including the receptors and associated mechanisms. Currently unanswered questions and areas for further exploration are discussed.